Padigma Kebijakan Politik Kerukunan Antaraagama Di Indonesia Pada Masa Orde Baru dan Masa Reformasi - Haidari, Amin (Tasamuh: Jurnal Studi Islam, 2017)
The concept of religious freedom is indeed ambiguous, even many commentators. This is understandable and inside and once outside used. At a time can be the foundation acts to dampen the expansionary activities faiths excessively, but at other times can also be used as a weapon to win the hearts of consumers and commodity markets spiritual rescue. In practice, the right to religious freedom is becoming one of the grain in the universal declaration of human rights, raises many problems. For this reason, there needs to be a new concept to replace the concept of religious freedom which he said was not relevant that, the concept of Interreligious Dialogue. If the concept of religious freedom presupposes the need to develop the theology of inter-religious harmony, it must be developed one step further into interreligious dialogue which requires the need for cooperation among religious believers in Indonesia.